Near-eye holographic 3D display and advanced amplitude-modulating encoding scheme for extended reality - Lee, Hyoung (2023)
Electronic holographic displays can reconstruct the optical wavefront of object light, exhibiting the most realistic three-dimensional (3D) images, in contrast to conventional stereoscopic displays. In this paper, we propose a novel, near-eye holographic 3D display (NEHD) applicable to AR/MR/holographic devices and experimentally demonstrate the proposed module’s performance with 360° full-viewed holographic 3D movie at 30 fps. To realize high-quality of reconstructed holographic 3D (H3D) images, we also propose an advanced amplitude-modulating (AM) encoding scheme suited for the proposed amplitude-modulating NEHD. We experimentally verify that the new hologram-encoding approach can improve the image quality of H3D reconstructions through quantitative statistical analyses, by using evaluation methods for H3D images that are suggested in the paper. Two holograms at different viewing directions of the same 3D scene are designed to be displayed onto the proposed NEHD prototype for two eyes of an observer, respectively. The presented techniques for the proposed NEHD enable the observer to experience the depth cue, a realistic accommodation effect, and high-quality H3D movies at each eye.